Childcare context and socio-emotional development in toddlers - a quantitative report from the FinnBrain Birth Cohort Study, Finland - Tervahartiala Katja; Nolvi Saara; Kataja Eeva-Leena; Seppalä Milka; Autere Tuomo-Artturi; Hakanen Hetti; Karlsson Hasse; Carter Alice; Karlsson Linnea; Korja Riikka (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Toddlerhood is a period of intensive and rapid socio-emotional development. The effects of different types of childcare settings on child development have been widely studied, but the results have often been contradictory. The aim of this study was to compare social competence and socio-emotional problems in two-year-old children (n = 1104; girls 47.2%) who were either participating in out-of-home, center-based childcare or were cared for at home by their parents in Finland. The results showed that mothers reported more internalizing symptoms in toddlers participating in out-of-home, center-based childcare when compared to children who were cared for at home. No differences regarding externalizing symptoms or social competence were found. Overall, the results suggest that out-of-home, center-based childcare is not associated with major differences in a toddler's socio-emotional development. More research is needed to investigate whether differences in the socio-emotional development of the children participating in different types of childcare develop later in childhood.